2020
DOI: 10.3390/molecules25153496
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Investigation of Novel Classes of 3-Carene-Derived Potent Inhibitors of TDP1

Abstract: Two novel structural types of tyrosyl-DNA phosphodiesterase 1 (TDP1) inhibitors with hexahydroisobenzofuran 11 and 3-oxabicyclo [3.3.1]nonane 12 scaffolds were discovered. These monoterpene-derived compounds were synthesized through preliminary isomerization of (+)-3-carene to (+)-2-carene followed by reaction with heteroaromatic aldehydes. All the compounds inhibit the TDP1 enzyme at micro- and submicromolar levels, with the most potent compound having an IC50 value of 0.65 μM. TDP1 is an important DNA repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…e.g., the aniline derivative 1 with a myrtenal moiety has inhibitory activity at submicromolar concentrations ( Figure 1 ) [ 16 ]; coumarin-based (-)-myrtenal derivative 2 potentiated the cytotoxicity of camptothecin in cancer cells [ 17 ]; it has also been shown that 3, comprising diazaadamantane and citronellal residues, inhibits Tdp1 with IC 50 (half maximal inhibitory concentration) values of ~15 µM [ 18 ]; geranyl derivative 4 enhances the topotecan antitumor effect in in vitro and in vivo tumor models [ 19 ]; octahydro-2 H -chromene-derived compound 5 was found to be an effective Tdp1 inhibitor with an IC 50 value of 2 µM [ 20 ]. Finally, isobenzofuran 6 , containing a thiophene fragment, has a synergistic effect with topotecan in wild type cells, but not in Tdp1 knockout cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…e.g., the aniline derivative 1 with a myrtenal moiety has inhibitory activity at submicromolar concentrations ( Figure 1 ) [ 16 ]; coumarin-based (-)-myrtenal derivative 2 potentiated the cytotoxicity of camptothecin in cancer cells [ 17 ]; it has also been shown that 3, comprising diazaadamantane and citronellal residues, inhibits Tdp1 with IC 50 (half maximal inhibitory concentration) values of ~15 µM [ 18 ]; geranyl derivative 4 enhances the topotecan antitumor effect in in vitro and in vivo tumor models [ 19 ]; octahydro-2 H -chromene-derived compound 5 was found to be an effective Tdp1 inhibitor with an IC 50 value of 2 µM [ 20 ]. Finally, isobenzofuran 6 , containing a thiophene fragment, has a synergistic effect with topotecan in wild type cells, but not in Tdp1 knockout cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned, we have previously shown that various Tdp1 inhibitors enhanced the cytotoxic and antitumor effects of topotecan [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. In this work, we also tested the ability of the berberrubine sultones to sensitize cells to the action of topotecan.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, Tdp1 is a promising therapeutic target, and its inhibitors are expected to significantly synergize the effects of current anti-tumor therapies, including topoisomerase poisons and other DNA damaging agents. Indeed, it was found that combined treatment of tumor cells with Tdp1 inhibitors and anticancer drugs camptothecin or topotecan greatly increased the activity of these pharmaceuticals in in vitro [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and in vivo [ 29 , 30 ] experiments. Nevertheless, to the best of our knowledge, no Tdp1 inhibitors have reached human clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratories have a long-standing interest in the development and validation of sensitizers for camptothecin-based chemotherapy drugs [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Specifically, our recent work indicated that TDP1 inhibitors may potentiate topotecan both in vitro and in vivo [31].…”
Section: Introductionmentioning
confidence: 99%